Protraction facial mask for the early treatment of Class III malocclusion. Literature Review - Argote - Quispe, Denise Milagros (2020)
Class III malocclusion is characterised by poor maxillary growth (maxillary retrognathism) or inadequate mandibular growth (mandibular prognathism) or a combination of both. The most frequent questions regarding Class III treatment are: when should it be performed and which appliance is most appropriate, as there is currently a variety of appliances, however there is little evidence available regarding effectiveness. Moderate evidence shows that early treatment with a face mask results in substantial improvements as well as highlighting that the timing of early treatment is crucial for a successful outcome. The objective of this literature review is to evaluate the effectiveness of the facial mask in the early treatment of Class III malocclusion.